2023
DOI: 10.1038/s41598-023-29481-4
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene: an antioxidant product reducing dithane toxicity in Allium cepa L.

Abstract: The current study was undertaken to assess the attenuating potential of lycopene against Dithane toxicity in Alliumcepa L. roots. A.cepa bulbs were arranged in 6 groups. The control group was treated with tap water while the other groups were treated with 215 mg/L lycopene, 430 mg/L lycopene, 500 mg/L Dithane, 500 mg/L Dithane + 215 mg/L lycopene and 500 mg/L Dithane + 430 mg/L lycopene, respectively. When the treatments were completed, growth inhibition, biochemical, genotoxicity and meristematic cell injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Through their actions, toxins disrupt homeostasis, alter gene expression, and cancer-related metabolic signalling pathways [ 224 ]. Research has demonstrated that lycopene as a dietary supplement effectively mitigates the deleterious effects of myco-, bacterial, and chemical toxins [ 225 ] [ 125 , 226 , 227 ], fungicides [ 228 ], pesticides [ 229 ], herbicides [ 230 ], and fluoride [ 231 ]. It is hypothesised that lycopene mediates protection against toxins through its potent antioxidant, chelating, and antiapoptotic properties [ 224 ].…”
Section: Lycopene: Protective Effects Against Toxinsmentioning
confidence: 99%
“…Through their actions, toxins disrupt homeostasis, alter gene expression, and cancer-related metabolic signalling pathways [ 224 ]. Research has demonstrated that lycopene as a dietary supplement effectively mitigates the deleterious effects of myco-, bacterial, and chemical toxins [ 225 ] [ 125 , 226 , 227 ], fungicides [ 228 ], pesticides [ 229 ], herbicides [ 230 ], and fluoride [ 231 ]. It is hypothesised that lycopene mediates protection against toxins through its potent antioxidant, chelating, and antiapoptotic properties [ 224 ].…”
Section: Lycopene: Protective Effects Against Toxinsmentioning
confidence: 99%
“…After absorption from food, it is mainly stored in the liver, prostate, and adrenals. It is also present in lower concentrations, e.g., in the brain and skin [3,26]. The adipose tissue contains more lycopene than serum because it is a lipophilic compound [25].…”
Section: Lycopenementioning
confidence: 99%
“…Allium cepa L. is an effective plant model for assessing the hazardous effects of environmental pollutants 26 29 . About 148 compounds have been evaluated by 164 Allium test and have shown 76% result similarities with other studies 30 .…”
Section: Introductionmentioning
confidence: 99%